2007
DOI: 10.1007/s00284-007-9042-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphate-Solubilizing Fluorescent Pseudomonads from the Rhizosphere of Seabuckthorn Growing in the Cold Deserts of Himalayas

Abstract: Isolation and characterization of fluorescent pseudomonads with high phosphate-solubilizing ability is reported from the alkaline and calcium-rich soils with low P availability in the cold desert region of Lahaul and Spiti in the trans-Himalayas of India. Of 216 phosphate-solubilizing isolates, 12 exhibiting high solubilization of tricalcium phosphate (TCP) in NBRIP liquid culture were identified as Pseudomonas trivialis, P. poae, P. fluorescens, and Pseudomonas spp. on the basis of phenotypic features, whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 24 publications
5
75
1
2
Order By: Relevance
“…Another subgroup harboring many efficient phosphatesolubilizing bacteria was subgroup 1g (with reference strain SBW25). There are other studies that have identified Pseudomonas strains closely related to SBW25 as strong P solubilizers (4,13). For future studies, it would be interesting to test strong phosphate solubilizers selected from subgroups 1d and 1g for efficacy in planta in comparison to strains of other phylogenetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Another subgroup harboring many efficient phosphatesolubilizing bacteria was subgroup 1g (with reference strain SBW25). There are other studies that have identified Pseudomonas strains closely related to SBW25 as strong P solubilizers (4,13). For future studies, it would be interesting to test strong phosphate solubilizers selected from subgroups 1d and 1g for efficacy in planta in comparison to strains of other phylogenetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this investigation is the reported phosphate solubilization and plant growth promotion by a psychrotolerant strain of Pseudomonas fragi CS11RH1. Earlier studies on phosphate solubilization/plant growth promotion by pseudomonads include P. fluorescens (Di Simine et al 1998), P. corrugata (Pandey & Palni 1998), P. aeruginosa (Musarrat et al 2000), P. stutzeri (Vazquez et al 2000), P. putida (Pandey et al 2008), P. rhizosphaerae , P. lutea (Peix et al 2004), P. trivialis and P. poae (Gulati et al 2008). P. fragi is commonly encountered in refrigerated dairy products and is distinguished from other pseudomonads by its inability to produce iron sequestering siderophores from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports on plant growth promotion by bacteria (Kucey et al, 1989) that have the ability to solubilize inorganic or organic P from soil after their inoculation in soil. Wani et al (2007c) reported a synergistic effects of PSB and N 2 -fixing bacteria on chickpea plants with the significant increase of grain yield and uptake of P and N. Larger quantities of the insoluble P became soluble after the addition of PSB (Subba Rao, 1984) and concurrently use of PSB as inoculants enhances plant P uptake and crop yield (Rodriguez and Fraga, 1999;Gulati et al, 2007). Strains were able to produce organic acids such as oxalic acid, malic acid, succinic acid and propionic acid from both soil and roots of aerobic rice.…”
Section: Discussionmentioning
confidence: 99%